2019
DOI: 10.1002/jia2.25359
|View full text |Cite
|
Sign up to set email alerts
|

Assessing risk for HIV infection among adolescent girls in South Africa: an evaluation of the VOICE risk score (HPTN 068)

Abstract: Introduction To maximize impact and minimize costs, antiretroviral pre‐exposure prophylaxis (PrEP) interventions should be offered to those at highest risk for HIV infection. The risk score derived from the VOICE trial is one tool currently being utilized to determine eligibility in adolescent PrEP trials in sub‐Saharan Africa. This study is aimed at evaluating the utility of the risk score in predicting HIV incidence among a cohort of adolescent girls in rural South Africa. Methods We utilized data from HIV P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
(23 reference statements)
0
27
0
Order By: Relevance
“… 17 , 18 The MTN-003/VOICE risk score was previously developed and externally validated in 3 cohorts of women aged 18–45 participating in clinical trials of HIV-1 prevention products in sub-Saharan Africa. 9 , 19 However, the VOICE risk score performed poorly among adolescent girls and young women in recent research, 20 suggesting that a different set of risk factors may be more predictive of HIV-1 acquisition among younger age groups. Given high HIV-1 incidence in this group of women, 1 risk scores tailored to their unique risk profile are needed.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 The MTN-003/VOICE risk score was previously developed and externally validated in 3 cohorts of women aged 18–45 participating in clinical trials of HIV-1 prevention products in sub-Saharan Africa. 9 , 19 However, the VOICE risk score performed poorly among adolescent girls and young women in recent research, 20 suggesting that a different set of risk factors may be more predictive of HIV-1 acquisition among younger age groups. Given high HIV-1 incidence in this group of women, 1 risk scores tailored to their unique risk profile are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies found that HIV incidence increased monotonically with the risk scores, except for Giovenco [25] (Table S6). Figure 5 shows the proportion of participants identified as high risk compared to the percentage of incident cases contributed by the high-risk group.…”
Section: Resultsmentioning
confidence: 99%
“…One additional conference abstract was available after initial screening, adding to a total of 13 risk score literature (9 peer-reviewed articles, 2 posters, 1 editorial letter, 1 abstract) that met the inclusion criteria and were included in this review (Figure 1) [5,6,[20][21][22][23][24][25][26][27][28][29][30]. Critical appraisal according to the PROBAST checklist concluded that one out of twelve models developed and two out of nine validated were of low risk of bias (Figure S1, Table S3 & S4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations